FORGIVENESS DAN PERSONALITY TRAIT PADA MAHASISWA - Alhad, Muhammad Afif; Herani, Ika; Nisa, Zahrotun; Silvia, Eka; Aji Nugroho, Mahardhika Cahyo (JURNAL TALENTA PSIKOLOGI, 2021)
Conflict could potentially occur in any interpersonal relationships. Everybody can actually experience conflict including undergraduate students, it is because they get involved in the dynamics of campus life. The conflicts experienced by college students are usually about love life, friendship, and family. Conflict will be resolved if the conflicting parties can sit together to find rational solutions and to forgive each other. The tendency to forgive others or forgiveness can be influenced by many factors. This study focused on personality type as an internal factor. Previous studies conducted in several countries showed that there were two types of personality that affect forgiveness, namely agreeableness and neuroticism. This study was conducted with the aim of proving whether those findings could probably work here in the Indonesian undergraduate student population. This study employed 807 participants attained through convenience sampling. The results of multiple regression analysis proved that forgiveness could be predicted by agreeableness and neuroticism. In detail it indicates that forgiveness would be performed by individuals with either a high level of agreeableness and a low level of neuroticism. Simultaneously agreeableness dan neuroticism explained 21% variance in forgiveness.